Paraspinal muscle hypotrophy and chronic discogenic low back pain - Truszczyńska-Baszak Aleksandra; Krauze Bruno; Tarnowski Adam (Sciendo, 2018)
Study aim: Low back pain is accompanied by deconditioning of trunk muscles due to pain limiting patients' physical activity, but so far it has not been explained whether the changes in the structure of muscles are the cause of disc disease or its result. The aim of the study was to analyze the prevalence of segmental paraspinal muscle hypotrophy in patients with chronic low back pain and sciatica. Material and methods: The study involved magnetic resonance imaging (MRI) of 40 patients: 20 women and 20 men aged from 30 to 47, mean 39.51 ± 3.73 years, with single level disc extrusion at L4-L5. The entire cross-sectional area of the paraspinal muscles, the adipose tissue area in the paraspinal muscles and the extensor muscle tissue area at the level of L4-L5 were measured and compared with the healthy L3-L4 level. T2-weighted axial slices were used to facilitate distinguishing between the muscle and the fat tissue. Results: Fat tissue ingrowth and paravertebral muscle tissue hypotrophy at the disc extrusion level were highly statistically significant (p < 0.001) compared to the healthy level. Conclusions: 1. Ingrowth of the adipose tissue into the muscle tissue occurs only at the level of disc extrusion. 2. It seems reasonable to introduce strengthening exercises after the resolution of pain in order to rebuild the muscles of the spine.